PERANCANGAN AUGMENTED REALITY FLASHCARD SEBAGAI MEDIA ALTERNATIF PEMBELAJARAN PENGENALAN HURUF BAGI SISWA KELAS 2 SDN PARUNG SERAB - Sukmawan, Awaludin; Widyananda Putra, Ricky (Kartala, 2025)
The Augmented Reality Flashcard media design as a media to support letter learning, combines Augmented Reality (AR) technology with traditional flash card games to create an interactive and fun learning experience. The main focus of this design is to increase reading interest and understanding of the alphabet in children through the use of attractive design characters. With the Design Thinking method, this creation starts from understanding the needs of users, namely children and educators, to produce a final product that is relevant and effective. It is hoped that the implementation of Augmented Reality Flashcard media can make a positive contribution to learning methods in elementary schools and help teachers deliver material in a more innovative way.